Pengaruh Pemberian Pijat Oksitosin untuk Memicu Produksi Asi pada Ibu Post Partum - Natalia Yeni; Ellyzabeth Sukmawati; Eddy Wibowo (Lembaga Pengembangan Kinerja Dosen, 2026)
Oxytocin massage is a technique used to stimulate the release of the hormone oxytocin, which plays a vital role in breastfeeding. Spinal massage stimulates the parasympathetic nervous system, which then triggers the release of oxytocin. This hormone causes contractions in the muscle cells surrounding the milk ducts, thereby promoting breast milk production. The purpose of this study was to determine the effect of oxytocin massage on increasing breast milk production in postpartum mothers. This study used a quantitative design with a quasi-experimental approach, namely a one-group pretest-posttest design. The study population was postpartum mothers with breast milk flow problems at the Bandarharjo Community Health Center, Semarang City. The sampling technique used was purposive sampling, where researchers selected samples based on certain characteristics. Data collection was carried out using a questionnaire. Data analysis used the Chi-Square test. The results of the study showed that the calculated Chi-Square value on the first day (62,000) was greater than the Chi-Square table (12,591), on the second day (54,866 > 23,684), and the third day (58,117 > 32,670). Based on these results, H0 was rejected and Ha was accepted, which means there was a significant effect of oxytocin massage on the smooth production of breast milk in postpartum mothers at the Bandarharjo Community Health Center.